2011
DOI: 10.1109/tnet.2011.2120618
|View full text |Cite
|
Sign up to set email alerts
|

On the Levy-Walk Nature of Human Mobility

Abstract: We report that human walks performed in outdoor settings of tens of kilometers resemble a truncated form of Levy walks commonly observed in animals such as monkeys, birds and jackals. Our study is based on about one thousand hours of GPS traces involving 44 volunteers in various outdoor settings including two different college campuses, a metropolitan area, a theme park and a state fair. This paper shows that many statistical features of human walks follow truncated power-law, showing evidence of scale-freedom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
478
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 898 publications
(497 citation statements)
references
References 46 publications
15
478
4
Order By: Relevance
“…Foraging movement patterns that fit closely to walks (1.1) known as Lévy flights [7] were identified in many living spieces ranging from micro-organisms to humans [4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20], although the reported scaling exponents varied substantially for different animals, in different environmental contexts. The rate of flight lengths decay in the population data is typically described by a power law with an exponential cut-off revealing that an exponential decay rate dominates for extremely long travels [13,21].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Foraging movement patterns that fit closely to walks (1.1) known as Lévy flights [7] were identified in many living spieces ranging from micro-organisms to humans [4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20], although the reported scaling exponents varied substantially for different animals, in different environmental contexts. The rate of flight lengths decay in the population data is typically described by a power law with an exponential cut-off revealing that an exponential decay rate dominates for extremely long travels [13,21].…”
Section: Introductionmentioning
confidence: 94%
“…The analysis of adaptive strategies instantaneously evolving in VE accentuates the key biological mechanisms of searching behaviour more vividly than the analysis of empirical data recorded in situ. Furthermore, in VE, we can study the mobility patterns of humans with extremely high resolution, up to the scales of millimetres and milliseconds, obtaining by far the most accurate data virtually comparable to either the scales of a few meters/tenth of seconds, kilometres per hours (in GPS tracking data; [19]), or the scale of a few thousand kilometres per week (in banknote travel patterns; [11]) discussed in the previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Among these unusual diffusion processes, Lévy flights have been extensively studied on lattices and continuous media [1,2] as they can display superdiffusion, so that the variance of the distance covered during the process grows superlinearly x 2 (t) ∝ t γ with γ > 1 at odds with linear diffusion for the Brownian motion [3,4]. This enhanced diffusion entails an efficient exploration of the space in which the diffusion process takes place: thus both in natural contexts and in artificial ones Lévy flights have emerged as a strategic choice for such an exploration and for search strategies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In the case of Lévy flights, the whole process relies on the divergence of the second moment of the jump probability distribution P ( ), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Here we relax that assumption and update our algorithm specification to include a prediction of the mobile device locations based on a model of human mobility patterns. Gonzalez et al [12] have shown that human mobility can be compared to a Levy walk with heavy-tail flight distribution and Rhee et al [13] have presented a truncated Levy walk model for the same. We use this truncated Levy walk mobility model for prediction of the mobile device locations.…”
Section: Introductionmentioning
confidence: 99%